The Influences of Masjid Agung Demak in Mataraman Court Mosques (1587–1775) - Nugraha, Wildan Bima Arya (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Mosque is a place of worship for Muslims. In addition to being a place of worship, the mosque is also a place for mixing architectural design and art or being a descendant of a line of mosque architectural designs. From the influence of other cultures to being a descendant of an architectural lineage. The purpose of this writing is to show that the Karaton Mataraman Mosque was indeed influenced by the Demak Grand Mosque in terms of layout and design. This can be seen from the Demak Grand Mosque, which was built in the second half of the 15th century AD, this mosque adopted the design and layout of traditional Javanese houses and Punden Berundak. This can be seen from the use of spatial planning and layout that is layered with levels. This design was adopted and used in the establishment of the Kotagede Kauman Mosque, the first mosque of Nagari Mataram around 1587 until the construction of the Jogjakarta Kauman Mosque in 1773, in addition, data and writings were also found that mentioned the flow of the building of the mosque which started from Liwan, then Serambi, then continuing with Pawestren, Regol, Kelir, Rana and Jagangan.